2005
DOI: 10.3758/bf03195328
|View full text |Cite
|
Sign up to set email alerts
|

On the role of verbalization during task set selection: Switching or serial order control?

Abstract: Recent task-switching work in which paper-and-pencil administered single-task lists were compared with task-alternation lists has demonstrated large increases in task-switch costs with concurrent articulatory suppression (AS), implicating a crucial role for verbalization during switching (Baddeley, Chincotta, & Adlam, 2001;Emerson & Miyake, 2003). Experiment 1 replicated this result, using computerized assessment, albeit with much smaller effect sizes than in the original reports. In Experiment 2, AS interfere… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

12
75
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 67 publications
(87 citation statements)
references
References 29 publications
12
75
0
Order By: Relevance
“…Such constraint is also evident in the experiment on the task span reported by Logan (2004b) which revealed that the task span (the number of tasks that could be remembered and correctly executed) was essentially not different from the memory span (the number of tasks that could be remembered). This proposal is also consistent with the findings reported by Bryck and Mayr (2005) which suggest that verbalization of sequential information in task switching is critical for maintenance of sequential courses of actions or sequential plans. These and other studies (Baddeley, Chincotta, & Adlam, 2001;Emerson & Miyake, 2003;Miyake, Emerson, Padilla, & Ahn, 2004;Saeki & Saito, 2009) strongly indicate that working memory forms a basis for task switching without implying that shortage of working memory capacity would completely disrupt task-switching performance.…”
Section: Modeling Assumptionssupporting
confidence: 91%
“…Such constraint is also evident in the experiment on the task span reported by Logan (2004b) which revealed that the task span (the number of tasks that could be remembered and correctly executed) was essentially not different from the memory span (the number of tasks that could be remembered). This proposal is also consistent with the findings reported by Bryck and Mayr (2005) which suggest that verbalization of sequential information in task switching is critical for maintenance of sequential courses of actions or sequential plans. These and other studies (Baddeley, Chincotta, & Adlam, 2001;Emerson & Miyake, 2003;Miyake, Emerson, Padilla, & Ahn, 2004;Saeki & Saito, 2009) strongly indicate that working memory forms a basis for task switching without implying that shortage of working memory capacity would completely disrupt task-switching performance.…”
Section: Modeling Assumptionssupporting
confidence: 91%
“…However, articulatory suppression had equivalent effects on switch trials and nonswitch trials and had no effect on the switching cost. Bryck and Mayr (2005) also examined the effects of articulatory suppression, using an alternating-runs paradigm, and demonstrated results similar to those described above. They suggested that a critical function of verbalization is the endogenous sequencing of tasks on the basis of the sequential characteristics of language.…”
mentioning
confidence: 73%
“…A large body of literature exists on the task-switching paradigm. However, in this study, we focused on a specific issue suggested by previous studies-namely, that verbal representations are useful mediators for efficient task-switching performance, especially in predictable and sequential task switching (Baddeley, Chincotta, & Adlam, 2001;Bryck & Mayr, 2005;Emerson & Miyake, 2003;Saeki & Saito, 2004a, 2004bSaeki, Saito, & Kawaguchi, 2006).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Local costs compare no-switch and switch trials (in which the relevant task differs from that of the previous trial) within mixed blocks only. Mixing and local costs have been shown to be sensitive to different variables (e.g., Bryck & Mayr, 2005;Mayr, 20019). Rubin and Meiran (2005) argued that mixing costs primarily reflect goal setting (which they also termed "task decision") because goal setting, but not switching, is present in no-switch trials, and neither goal-setting demand nor switching demand is present in simple blocks.…”
mentioning
confidence: 99%